Locoregional Combined With Systemic Therapies for Advanced Hepatocellular Carcinoma: An Inevitable Trend of Rapid Development - Li, Xin; Wang, Yaxi; Ye, Xin; Liang, Ping (Frontiers in Molecular Biosciences, 2021)
Despite the application of anti-viral drugs and improved surveillance tools, the number of patients diagnosed with hepatocellular carcinoma (HCC) at an advanced stage and with a dismal prognosis is still on the rise. Systemic treatment with multiple multi-targeted tyrosine kinase inhibitors (TKIs), such as sorafenib, has been a widely utilized approach for a decade. In addition, the use of a combination of TKIs with other types of compounds, including immune checkpoint inhibitors (ICIs) and antiangiogenic inhibitors, has shown efficacy in treating advanced HCC. However, the presence of intolerable adverse events, low disease response and control rates, and relative short overall survival of such combinatory therapies makes novel or optimized therapies for advance HCC urgently needed. Locoregional therapy (transarterial chemoembolization and thermal ablation) can destroy primary tumors and decrease tumor burden and is widely used for HCC management. This type of treatment modality can result in local hypoxia and increased vascular permeability, inducing immunogenic effects by releasing tumor antigens from dying cancer cells and producing damage-associated molecular patterns that facilitate antiangiogenic therapy and antitumor immunity. The combination of systemic and locoregional therapies may further produce synergistic effects without overlapping toxicity that can improve prognoses for advanced HCC. In preliminary studies, several combinations of therapeutic modes were exhibited promising levels of safety, feasibility, and antitumor effects in a clinical setting and have thus garnered much attention. This review aims to provide a comprehensive, up-to-date overview of the underlying mechanisms of combined systemic and locoregional therapies in the treatment of advanced HCC, commenting on both their current status and future direction.